2012
DOI: 10.1111/j.1447-0756.2011.01692.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal fluid creatinine for the detection of premature rupture of membranes

Abstract: Aim: The aim of this study was to evaluate the reliability of vaginal fluid creatinine for the diagnosis of premature rupture of membranes (PROM). Material and Methods: A total of 180 pregnant women were enrolled in the study. Group I (confirmed group) consisted of 60 women with a diagnosis of rupture of membranes confirmed by visualization of fluid passing from the cervical canal. Group II (suspected group) consisted of 60 women with a complaint of vaginal fluid leakage but without obvious amniotic fluid flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
3
10
1
Order By: Relevance
“…Furthermore, in the study in which Zanjani et al [20] confirmed PROM diagnosis in the speculum examination according to the presence of pooling and the nitrazine test result, they found 96.5% sensitivity, 100% specificity, 100% positive predictive value and 96.8% negative predictive value when the cut-off value of creatinine in the vaginal flushing fluid was taken as 0.5 mg/dl. However, the high false positivity rate of nitrazine test in the PROM diagnosis due to the possibility of change in vaginal pH in the presence of blood, semen or infection such as bacterial vaginosis has paved the way for other studies.. Sekhavat et al [16] used fern test and the detection of pooling in the speculum examination to confirm the PROM diagnosis test on the grounds that nitrazine test has a high rate of false positivity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, in the study in which Zanjani et al [20] confirmed PROM diagnosis in the speculum examination according to the presence of pooling and the nitrazine test result, they found 96.5% sensitivity, 100% specificity, 100% positive predictive value and 96.8% negative predictive value when the cut-off value of creatinine in the vaginal flushing fluid was taken as 0.5 mg/dl. However, the high false positivity rate of nitrazine test in the PROM diagnosis due to the possibility of change in vaginal pH in the presence of blood, semen or infection such as bacterial vaginosis has paved the way for other studies.. Sekhavat et al [16] used fern test and the detection of pooling in the speculum examination to confirm the PROM diagnosis test on the grounds that nitrazine test has a high rate of false positivity.…”
Section: Discussionmentioning
confidence: 98%
“…The study performed by Gürbüz et al [12] also observed the same level to P a g e / S a y f a | 426 be 0.026 (0.029) mg/dl in the group whose water did not break, and 0.70 (0.55) mg/dl in the group whose water broke. It has been suggested in previous studies that the creatinine assessment in vaginal flushing fluid can be used as a marker for diagnosis when PROM is clinically suspected in the speculum examination [12,16,19,20,30]. Firstly, the study conducted by Li Hy et al [29] found that hCG, AFP and creatinine concentrations were high in amniotic fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-hCG is also a substance produced by trophoblastic tissue, found in different concentrations in maternal blood, urine, and amniotic fluid, and is easy to detect. [13] The presence of these two substances in low concentrations in vaginal secretions and the increase in the concentration in the vagina after amniotic drainage in PROM means that the use of these substances may be appropriate in the diagnosis of PROM. In our study, we investigated the place of β-hCG and creatinine values in vaginal washing fluid in the diagnosis of PROM.…”
Section: Discussionmentioning
confidence: 99%
“…Zanjani and Haghighi analyzed the sensitivity, specificity, PPV, and NPV of varying levels of vaginal fluid creatinine. 5 Lee et al had done a study on the measurement of placental alpha-microglobulin-1 in cervicovaginal discharge to diagnose a ROM. 6 They had observed 184 women of GA 11-42 weeks, ROM was diagnosed in 76% using conventional clinical assessment (nitrazine test) and 88% using placental alpha-microglobulin-1.…”
Section: Discussionmentioning
confidence: 99%